If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5g + -2h = 3G + -1 Reorder the terms: 5g + -2h = -1 + 3G Solving 5g + -2h = -1 + 3G Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '2h' to each side of the equation. 5g + -2h + 2h = -1 + 3G + 2h Combine like terms: -2h + 2h = 0 5g + 0 = -1 + 3G + 2h 5g = -1 + 3G + 2h Divide each side by '5'. g = -0.2 + 0.6G + 0.4h Simplifying g = -0.2 + 0.6G + 0.4h
| r=2h+2zsolveh | | -10u+8=7u+12 | | 58/27=10/x | | (7x+4)(x-1)=0 | | 3.2x=16 | | -10u+8=7u+13 | | .035x=5 | | H(t)=-16x^2+VoT+hi | | 6(11)+1=180 | | 9c^2+18c-16=o | | .02x=5 | | 0.3x-0.5x-7=-21 | | 138*3d=d | | 7x+10-6x=20 | | x+(x+30)=4000 | | 1x=1x+6 | | .33(x+3)+.17(x-6)=x+3 | | 5m-23=-28+6m | | 4(5-a)+2(3a+1)= | | .33(x+3)+.16(x-6)=x+3 | | ln(5x-3)=2 | | 138*3d= | | 9y+5y+y= | | W^2+5w-50=0 | | 4×3/4 | | 3(x-1)+3=13 | | 5x+6=5(x+7) | | 5x-25=26+2x | | 4×3/8 | | (8-3x)/(2√(4-x)) | | -10r=-40 | | 13-9x=26-16x |